Analisis Konsonan (الصوامت) dalam QS al-Ma‘ūn: Kajian Makhraj dan Sifat Huruf Berdasarkan Tartil Syekh as-Sudais - Anam, Rifky Khoirul (Maliki Interdisciplinary Journal, 2025)
This study examines the arabic consonants (ṣawāmit) in Surah al-Mā‘ūn using a phonetic-linguistic approach, focusing on makhārij and consonantal features as produced in the tartil recitation of Shaykh Abdurrahman as-Sudais. The research employs a descriptive–phonetic method by repeatedly analyzing the recorded recitation, identifying places and manners of articulation, and comparing them with classical tajwīd principles. The findings indicate a high level of consistency in the articulation of features such as shiddah, rakhāwah, hams, jahr, isti‘lā’, and ithbāq, which correspond closely to modern phonetic categories such as stops, fricatives, nasals, laterals, and emphatic consonants. The analysis also shows that short-voweled consonants display controlled duration reduction without loss of articulatory accuracy, while emphatic sounds maintain stable pharyngeal resonance. This research affirms that integrating tajwīd and modern phonetics offers a more precise understanding of articulation quality in Qur’anic recitation.